Elevated Risk of Nicotine Dependence Among Sib-pairs Discordant for Maternal Smoking During Pregnancy: Evidence from a 40-year Longitudinal Study. Issue 3 (May 2015) - Shenassa, Edmond D.; Papandonatos, George D.; Rogers, Michelle L.; Buka, Stephen L.
Abstract : Background: Compelling evidence links maternal smoking during pregnancy with elevated risk of nicotine dependence among the offspring. However, no study to date has examined the maternal smoking during pregnancy-nicotine dependence link among sibling-pairs discordant for maternal smoking during pregnancy. We tested two hypotheses that, if supported, suggest that the maternal smoking during pregnancy-nicotine dependence link may be physiologically mediated. Methods: Study participants were adult offspring of women enrolled in the Providence and Boston sites of the Collaborative Perinatal Project (1959–1966). Approximately 10% of these adult offspring (average age: 39.6 years) were enrolled in the New England Family Study (n = 1, 783), a follow-up study that oversampled families with multiple siblings. Logistic regression models predicting maternal smoking during pregnancy risk on various prospectively collected smoking and marijuana use outcomes, including nicotine dependence, were fit using models that allowed between-mother effects of maternal smoking during pregnancy exposure to differ from within-mother effects. In the absence of significant effect heterogeneity, we calculated a combined estimate. Results: Maternal smoking during pregnancy predicted progression from weekly smoking to nicotine dependence (odds ratio = 1.4 [95% confidence interval = 1.2, 1.8]), but not weekly smoking or progression to marijuana dependence. Conclusions: Current evidence from sibling-pairs discordant for maternal smoking during pregnancy is consistent with previous reports of a dose–response association between maternal smoking during pregnancy and nicotine dependence, as well as of up-regulation of nicotine receptors among animals exposed to maternal smoking during pregnancy. Together, they provide support for the existence of a physiologically mediated link between maternal smoking during pregnancy and nicotine dependence.